Differential microRNAs profile analysis in pericoronary adipose tissue adjacent to atherosclerotic plaque. (14th October 2021) - Marketou, M; Plevritaki, A; Kontaraki, J; Kalogerakos, P; Kochiadakis, G; Anastasiou, I; Papadaki, S; Papadopoulos, D; Maragkoudakis, S; Parthenakis, F; Lazopoulos, G
Abstract: Background: Pericoronary adipose tissue (PCAT) regulates arterial homeostasis, is considered to act in paracrine manner, and plays a role in the pathogenesis of atherosclerosis. PCAT may be a source of microRNAs (miRs) that target other tissues and act as messengers for intercellular communication. In this study, we investigated whether the PCATsurrounding coronary occlusive atherosclerotic lesions shows specific miRs expression patterns compared to PCAT surrounding segments without significant atherosclerosis (plaque-free segments). We evaluated expression of miRs that are known to be implicated in the pathophysiology of atherosclerotic disease. Methods: We included 40 patients (38 men, aged 62±12 years old) with 3-vessel coronary artery disease who underwent elective coronary bypass surgery. The PCAT was harvested from two sites: adjacent to coronary occlusive atheroscleroticlesion and plaque-free segment. miR-133a, miR-21, miR-26b, miR-9 and miR-143 expression levels in PCAT cells were quantified by real-time reverse transcription polymerase chain reaction. Results: PCAT analysis revealed a significant downregulation of miR-133a levels in periplaque samples compared to those that were not adjacent to atheroscrerotic plaque (35.4±4.3 versus 87.2±130.5, p=0.03). We also found a significant decrease of miR-143 expression in segments adjacent to plaque compared to those surrounding plaque-free coronary artery (72.6±14.3 versus 213.2±222.5, p=0.01). No significant differences between the two sites were observed in PCAT expression of miR-21, miR-26b, miR-9 (170.7±205 versus 130.9±303.2, 129.8±64.3 versus 200.2±330.6, 40±0.2 versus 30.2±3.6, respectively, p=NS for all). Conclusions: miR-133a and miR-143 expression in PCAT surrounding coronary occlusive atherosclerotic lesions were significantly downregulated compared to PCAT surrounding segments without significant atherosclerosis. Our study opens new perspectives in the role of PCAT in the pathophysiological mechanisms and the treatment of atherosclerotic disease and should be further investigated. FUNDunding Acknowledgement: Type of funding sources: None.